Quick Services - Wala Amjad Faqeh (My University, 2011)
We have developed mobile application . This project must get all information that considers important part in our life such as news, currency and weather. So must supply this information in fast and cheap method. The project contains client and server to offer the goals of project.This project supply user the services of news, weather, currency, and another services from the server, without pay money, and for every user that around this server. This used for all mobiles (old, new, complex and simple).

We have developed mobile application . This project must get all information that considers important part in our life such as news, currency and weather. So must supply this information in fast and cheap method. The project contains client and server to offer the goals of project. This project supply user the services of news, weather, currency, and another services from the server, without pay money, and for every user that around this server. This used for all mobiles (old, new, complex and simple).
Quick Services